Phylogeographical Variation of Chloroplast DNA in Cork Oak (Quercus suber) (Annals of Botany)
• Background and Aims In the last decades, the geographical location of the centre of origin of Quercus suber (cork oak), a strictly western Mediterranean oak species, has been the subject of controversy.• Methods RFLP variation over the whole chloroplast DNA molecule and PCR–RFLPs over seven specific cpDNA fragments were analysed phylogeographically to reconstruct the evolutionary history of cork oak.• Key Results Nine chlorotypes of the ‘suber’ cpDNA lineage were identified throughout the species range. Using closely related Mediterranean oak species as outgroup, the chlorotypes showed a clear phylogeographical pattern of three groups corresponding to potential glacial refuges in Italy, North Africa and Iberia. The most ancestral and recent groups were observed in populations located in the eastern and western parts of the species range, respectively. Several unrelated chlorotypes of the ‘ilex’ cpDNA lineage were also identified in specific western areas.• Conclusions The results support a Middle-Eastern or a central Mediterranean origin for cork oak with subsequent westward colonization during the Tertiary Period, and suggest that the ‘ilex’ chlorotype variation does not reflect entirely cytoplasmic introgression by Q. ilex but originated partly in Q. suber.
10.1093/aob/mci237